Analisis Instrumen Kinerja Matematika Dengan Menggunakan Metode Exploratory Factor Analysis (EFA) - Muhammad Rijali Rais (Jurnal Sinar Edukasi, 2022)
This research aims to develop assessment of the circle material of 8th grade which is valid, reliable and practical. The development procedure includes three main stages, including preliminary stage, development stage and evaluation stage, by adopting development model of Djemari Mardhapi. The sample of the research was VIII grade students, amounting to 62 students of SMP Negeri 1 Takengon. The content validity was performed by expert judgment which was analyzed by using Aiken's V formula, the reliability of expert judgment was analyzed by using Eble formula through Two Way Anova. The constructs validity by using Exploratory Factor Analysis (EFA) and the reliability of the test was analyzed by using Alpha formula proved by the SPSS v.18 program. The results of the content validity indicate that all developed items test are valued > 0.3 and stated having adequate content validity. The reliability result of expert judgment obtains a coefficient > 0.6 that indicates that the three experts are consistent in providing an assessment. The results of construct validity obtain KMO coefficient above 0.5 so that the test item can be analyzed further. The estimation result of alpha reliability obtains coefficient of 0.748 with reliability coefficient category which is acceptable. The results of practicality test show the developed performance test is in the very practical category.